Islamic Management and Leadership in Kindergarten, Raudhatul Athfal, and Aisyiyah Bustanul Athfal - Yuda, Roky Darma; Syafnan; M. Asro’i Rambe (RADINKA JOURNAL OF SCIENCE AND SYSTEMATIC LITERATURE REVIEW, 2024)
Leadership management in Kindergarten RA and ABA is often faced with various challenges, both in terms of human resources, facilities, and parental involvement. This study dives into how Islamic management and leadership are applied in TK (Kindergartens), RA (Raudhatul Athfal), and ABA (Aisyiyah Bustanul Athfal) to create a nurturing educational environment for young children. By using a historical and qualitative approach, it uncovers leadership styles, challenges, and practical solutions in these institutions. The results show that blending Islamic values with modern management practices can shape a generation of well-rounded, strong-character individuals.